Sanksi Hukum Terhadap Tindak Pidana Menjual Kepada Umum Ciptaan Hasil Pelanggaran Hak Cipta - Adnan, Muhammad Ali (Universitas Islam Sumatera Utara, 2022)
The cause of the criminal act of selling to the public the creation of the result of copyright infringement is to take shortcuts to get the most profit, the legal sanction imposed by the court has been too light, by committing the violation, the tax on the product of the violation result is not need to be paid to the government, and the last is the low level of community education. Legal sanctions for the crime of selling to the public the creation of the result of copyright infringement is the imposition of criminal sanction in the form of imprisonment and fine of criminal to perpetrator of crime selling to public creation of violation result of copyright of threatened criminal sanction is punishable by imprisonment maximum 5 ( five) years and / or a fine of not more than Rp 500,000,000 (five hundred million rupiahs). To avoid the occurrence of criminal act of selling to public creation result of copyright infringement should government together with police can do socialization to society about penal effect of law if society still sell to public creation result of violation result of copyright. Keywords : Legal Sanctions, Criminal Acts, Solution Infringement